The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/pharmaceutics13111982
|View full text |Cite
|
Sign up to set email alerts
|

Manganese-Doped N-Hydroxyphthalimide-Derived Carbon Dots—Theranostics Applications in Experimental Breast Cancer Models

Abstract: Background: Theranostics, a novel concept in medicine, is based on the use of an agent for simultaneous diagnosis and treatment. Nanomaterials provide promising novel approaches to theranostics. Carbon Dots have been shown to exhibit anti-tumoral properties in various cancer models. The aim of the present study is to develop gadolinium, Fe3+, and Mn2+-doped N-hydroxyphthalimide-derived Carbon Dots. The resulted doped Carbon Dots should preserve the anti-tumoral properties while gaining magnetic resonance imagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…A good MRI signal may afford to confirm the targeting properties of MNP-P-FA1, which is in direct connection with longitudinal (T1) or transversal (T2) relaxation times. With the help of the Nucline software of the instrument, the longitudinal and transversal relaxivities, r1 and r2 , respectively, were calculated as the slope of the linear regression of R1 (1/T1) and R2 (1/T2) on the range of sample concentrations, similar to a previous study we have published [ 80 , 81 ]. The samples were prepared using the corresponding dispersions in PBS (pH 7.4) of MNP, MNP-P and MNP-P-FA1, by adding the calculated volume in 1% agarose (at 45 °C) to gain the concentration of Fe 3+ in the range of 0.01 ÷ 0.08 mM.…”
Section: Methodsmentioning
confidence: 99%
“…A good MRI signal may afford to confirm the targeting properties of MNP-P-FA1, which is in direct connection with longitudinal (T1) or transversal (T2) relaxation times. With the help of the Nucline software of the instrument, the longitudinal and transversal relaxivities, r1 and r2 , respectively, were calculated as the slope of the linear regression of R1 (1/T1) and R2 (1/T2) on the range of sample concentrations, similar to a previous study we have published [ 80 , 81 ]. The samples were prepared using the corresponding dispersions in PBS (pH 7.4) of MNP, MNP-P and MNP-P-FA1, by adding the calculated volume in 1% agarose (at 45 °C) to gain the concentration of Fe 3+ in the range of 0.01 ÷ 0.08 mM.…”
Section: Methodsmentioning
confidence: 99%
“…However, it has been reported [55] that even small amounts of CAs comparable to the relaxation time changes presented in this article, may provide good MRI contrast. Although there are several studies that have shown the biological compatibility and low toxicity of Mn-doped CDs [39,42,56], this is still a controversial issue requiring more research. Additionally, CAs less than 6 nm have been shown to be easily excreted by the kidneys and therefore can be administered intravenously, while larger particles are suitable for diagnoses of the gastrointestinal tract [47].…”
Section: Mr Performancementioning
confidence: 99%
“…It is seen that the signals in the 600-800 nm spectral region are almost the same, thus, the optical density in the 600-700 nm spectral region originates from absorption by CDs; Figure S6: Dependence of r1 and r2 relaxivities on the ratio of the peak 1 and peak 2 in Mn 2p 3/2 band areas taken from Table S3; Table S1: Synthesis conditions and composition of CDs; Table S2: Height distribution parameters of CDs from statistical analysis of AFM images; Table S3: Optical properties of CDs; Table S4: Deconvolution parameters for Mn 2p 3/2 band; Table S5: Characteristics of Mn-based contrast agents. References [28,39,[41][42][43][56][57][58][59][60][61] are cited in the Supplementary Materials.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…Magnetic CDs can be used as FL/MRI bimodal imaging probes in tumor diagnosis. , Shang et al prepared Gd-CDs with an emission wavelength of 614 nm and r 1 of 12.21 mM –1 s –1 for in vivo FL/MRI bimodal imaging . The T 1 images of tumor sites were brighter, and the fluorescence intensity was higher than that of normal tissues after the Gd-CDs injection in mice.…”
Section: Mechanisms Of Magnetic Cds In Bimodal Diagnosis and Treatmentmentioning
confidence: 99%